2022
DOI: 10.3390/ijerph19031095
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Lockdown on Glycaemic Control and Lipid Profile in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: The impact of the COVID-19 lockdown on glycaemic control and other metabolic parameters in patients with type 2 diabetes is still evolving. Aim: This systematic review and meta-analysis aims to examine the effects of COVID-19 lockdown on glycaemic control and lipid profile in patients with type 2 diabetes. Methods: The PRISMA framework was the method used to conduct the systematic review and meta-analysis, and the search strategy was based on the population, intervention, control and outcome (PICO) model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
4
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 36 publications
4
63
4
6
Order By: Relevance
“…As a consequence, some participants declared difficulty in performing basic tasks (i.e., cleaning the house, climbing stairs). Overall, the findings of a meta-analysis showed that COVID-19 lockdowns resulted in a significant increase in the levels of glycated haemoglobin (0.34%; 95% CI: 0.30–0.38), fasting plasma glucose (7.19 mg/dL; 95% CI: 5.28–9.10) and body mass index (1.13 kg/m 2 ; 95% CI: 0.99–1.28) in patients with T2DM [ 9 ]. Obesity is a significant risk factor for increased morbidity and mortality in people with T2DM, whereas reduction in body weight or the prevention of weight gain confers significant benefits in glycaemic and blood pressure control [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, some participants declared difficulty in performing basic tasks (i.e., cleaning the house, climbing stairs). Overall, the findings of a meta-analysis showed that COVID-19 lockdowns resulted in a significant increase in the levels of glycated haemoglobin (0.34%; 95% CI: 0.30–0.38), fasting plasma glucose (7.19 mg/dL; 95% CI: 5.28–9.10) and body mass index (1.13 kg/m 2 ; 95% CI: 0.99–1.28) in patients with T2DM [ 9 ]. Obesity is a significant risk factor for increased morbidity and mortality in people with T2DM, whereas reduction in body weight or the prevention of weight gain confers significant benefits in glycaemic and blood pressure control [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) comprises 90–95% of all diabetes cases [ 7 ]. Such worrying data confirm this disease as being a significant global challenge that may be exacerbated by the consequences of COVID-19 [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Experienced stress and lifestyle changes have been associated with increased body weight and HbA1c levels [37] . In the systematic review and meta-analysis study of Ojo et al (2022), they stated that glycosylated hemoglobin, fasting glucose and body mass index levels increased in patients with type 2 diabetes during the quarantine period compared to pre-COVID-19 [38] . DM management includes many factors that make compliance difficult for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the impact of a national lockdown on long-term glucose controls using glycated hemoglobin (HbA 1c ) and other metabolic parameters among T2D yield conflicting results. 4,5 The aim of this study was to investigate the impact of the national lockdown on regularly scheduled clinic visitation and changes in biochemical parameters among patients with T2D.…”
Section: Introductionmentioning
confidence: 99%